Appling tracking game system to measure user behavior toward cybersecurity policies - Alissa, Khalid Adnan; Aldeeb, Bashar Abedalmohdi; Alshehri, Hanan Abdullah; Dahdouh, Shahad Abdulaziz; Alsubaie, Basstaa Mohammad; Alghamdi, Afnan Mohammad; Alkenani, Moath Khaireddin; Alsmadi, Mutasem Khalil (Institute of Advanced Engineering and Science, 2022)
Institutions wrestle to protect their information from threats and cybercrime. Therefore, it is dedicating a great deal of their concern to improving the information security infrastructure. Users’ behaviors were explored by applying traditional questionnaire as a research instrument in data collocate process. But researchers usually suffer from a lack of respondents' credibility when asking someone to fill out a questionnaire, and the credibility may decline further if the research topic relates to aspects of the use and implementation of information security policies. Therefore, there is insufficient reliability of the respondent's answers to the questionnaire’s questions, and the responses might not reflect the actual behavior based on the human bias when facing the problems theoretically. The current study creates a new idea to track and study the behavior of the respondents by building a tracking game system aligned with the questionnaire whose results are required to be known. The system will allow the respondent to answer the survey questions related to the compliance with the information security policies by tracking their behavior while using the system.